Exit from dormancy provokes DNA-damage-induced attrition in haematopoietic stem cells - Walter, Dagmar; Lier, Amelie; Geiselhart, Anja; Thalheimer, Frederic; Huntscha, Sina; Sobotta, Mirko Christoph; Moehrle, Bettina; Brocks, David; Bayındır-Buchhalter, İrem; Kaschutnig, Paul Emanuel; Muedder, Katja; Klein, Corinna; et al. (Nature, 2015)
Here, DNA damage is shown to occur as a direct consequence of inducing haematopoietic stem cells to exit quiescence in response to conditions of stress; in mice with mutations modelling those seen in Fanconi anaemia, this leads to a complete collapse of the haematopoietic system.
Gesehen am 26.06.2020